Prognostic analysis of extrameningeal solitary fibrous tumor using the modified Demicco model: a clinicopathologic study of 111 Chinese cases - Yao, Chen-chen; Zhou, Jian; Li, Xiao; Yang, Jun; Chen, Gang; Wei, Jia; Fan, Qin-he; Gong, Qi-xing (Frontiers in Oncology, 2024)
covering the period from 2010 to 2020, were thoroughly analyzed. The tumors were classified using the mDemicco model. Immunohistochemical evaluation of P16 and P53, molecular detection of TP53 and TERT promoter mutation, and fluorescence in situ hybridization for CDKN2A gene alterations were performed. Statistical methods were utilized to assess the associations between clinicopathological or molecular factors and prognosis.Results: Histologically, only one parameter, the mitotic count, exhibited a statistical correlation with progression-free survival (PFS) and overall survival (OS). During the Kaplan-Meier analysis, the variation in PFS among the different risk groups exhibited a notable trend towards statistical significance. Nevertheless, 3 out of 74 patients classified as low-risk SFTs and 7 out of 21 patients classified as intermediate-risk exhibited disease progression. Among the 5 patients with TP53 mutations and/or mutant-type P53 immunophenotype, 3 experienced disease progression, including 2 intermediate-risk patients. Additionally, among the 4 patients with TERT promoter mutations who were followed up, 3 showed progression, including 2 intermediate-risk patients. Moreover, it was observed that hemizygous loss of CDKN2A was detected in more than 30% of one case, yet the patient exhibited a favorable survival outcome.The mDemicco risk model exhibits certain limitations when dealing with smaller tumor sizes, younger age groups, and occurrences of malignant and dedifferentiated SFTs. Furthermore, molecular factors, such as TP53 or TERT promoter mutations, may identify intermediate-risk SFTs with poorer prognoses.